Protein Analysis of chrysomya megacephala Maggot Meal - Sing, K.W.; Sofian-Azirun, Mohd; Tayyab, S. (2012)
Protein content of Chysomya megacephala maggot meal extract was determined using different colorimetric methods such as biuret method, dye-binding method and Lowry method. Protein estimation was performed after dissolution of maggot powder in 0.06 M sodium phosphate buffer (pH 7.0) both in the absence and the presence of 1 sodium dodecyl sulphate (SDS). Alternatively, use of color reagent was made both before and after centrifugation of the dissolved mixture. Whereas dye-binding method could not be performed in presence of SDS due to its interference, both biuret method and Lowry method were employed using standard curves in presence of 1 SDS. Two other methods, namely, Warburg-Christian method and semi-micro Kjeldahl method were also used to determine protein concentration. Both inclusion of SDS and addition of color reagents before centrifugation of the dissolved sample showed a significant increase in the percentage protein content compared to the results obtained under normal condition. A comparison of all these results suggested the use of biuret method and Lowry method under specific conditions as the substitute for semi-micro Kjeldahl method for protein estimation. The SDSpolyacryalmide gel electrophoresis of maggot meal extract showed the presence of both small and medium sized proteins ranging in molecular weights from 17 kDa to 83 kDa. Maggot meal powder was also found rich in essential amino acids as determined by amino acid analysis. Taken together, all these results suggested the suitability of C. megacephala maggot meal as a good protein source in animal feed.